Self-directed learning readiness of recent medical graduates / Mohamad Nabil Mohd Noor - Mohamad Nabil, Mohd Noor (2021)
Self-directed learning occurs when teachers empower learners to take control of their learning. This method has been highlighted in medical education to promote lifelong learning for physicians to adapt to the ever-changing field of medicine. Past researchers have focused on undergraduate medical students' self-directed learning readiness and suggested further studies for the population after graduation. The present study aims to measure the level of self-directed learning readiness amongst recent medical graduates in Malaysia. 371 Malaysian doctors who recently graduated within the past 18 months participated in this study and completed Guglielmino’s Self-Directed Learning Readiness Scale. Mean score was computed to compare the Self-Directed Learning Readiness scores between different age groups and Independent samples T-tests were used to compare the scores between genders and between employment statuses. The mean Self-Directed Learning Readiness Scale score was 215.18 (SD = 22.62) which is similar to the population average. There was no significant difference in the scores between age groups and gender. The scores between employed and unemployed participants showed no significance, but employed graduates obtained higher scores than their unemployed counterparts. Medical graduates should be trained to be highly self-directed to be independent in their learning. This study implies the importance of medical education institutions to incorporate instructional delivery that promotes self-directed learning and provide activities that can boost self-directed learning after graduation and during service. Graduates should be guided in planning their career paths to ensure an optimum level of self-directed learning.